Evaluation of bacterial antagonists for the management of rhizome rot of cardamom (Elettaria cardamomum Maton) - Dhanya M K, Sivakumar G, Josephrajkumar A (Journal of Spices and Aromatic Crops, 2012)
Among the 90 rhizobacterial isolates screened against rhizome rot pathogens (Pythium vexans, Fusarium oxysporum and Rhizoctonia solani) of cardamom (Elettaria cardamomum) two bacterial strains viz., Pseudomonas fluorescens Pf 51 and Bacillus subtilis B45 were highly inhibitory. P. fluorescens Pf 51 exhibited highest inhibition (42.5%, 44.2% and 41.4% respectively) against P. vexans, F. oxysporum and R. solani. B. subtilis B45 also exhibited highest inhibition (43.2%, 41.2% and 42.4% respectively) against these three pathogens. P. fluorescens Pf51 was compatible with B. subtilis Bs 45. Peat formulation supported the survival of both the strains up to 270 days with a viable population of 4.3 × 107 cfu g-1 and 6.2 × 107 cfu g-1 respectively. Application of antagonists in combination with rhizome bacterization and soil application resulted in 54.0% reduction in rhizome rot over control as compared to single method such as rhizome bacterization (43.0%) or soil application (39.0%). Application of copper oxychloride and carbendazim resulted in 68.0% reduction of rhizome rot. Maximum height (167.21 cm) and number of tillers (30.14) were recorded due to the application of mixture of both the strains through rhizome bacterization and soil application.